SURVEI KESEHATAN HIDUNG PADA MASYARAKAT PESISIR PANTAI BAHU - Tumbol, Andreas R.; Tumbel, R. E. C.; Palandeng, Ora I. (Universitas Sam Ratulangi, 2015)
Abstract: Human’s health can be affected by environment and human’s behaviour. Nose is an important part of human that can be a shield of environmental disadvantages. Thisa study aimed to obtain nose health of people of Bahu coastal area. This was a descriptive observasional study with a cross sectional design. The subjects of this study were people living at Bahu coastal area. There were 31 respondents consisting of 12 men and 19 women. Nose examination showed normal result in 19 respondents and abnormality in 12 respondents. In nasal passage examination, 3.2% respondents showed narrow nasal cavities. In nasal turbinate examination, swollen conchae were found in 6.5% of respondents; swollen and pale conchae 6.5%; swollen, pale, and hypertrophic conchae in right turbinate 3.2% meanwhile in left turbinate 6.5%; and swollen, hyperemic, and hypertrophic conchae in right and left turbinate 3.2%. Hypertrophic conchae in right turbinate was 3.2% while in left turbinate was 6.5%. Pale and hypertrophic conchae in right and left turbinate was 3.2%. In nasal mucosa examination, hyperemic mucosa was 3.2% and bluish mucosa was 16.1%. In secretion examination, serous and mucoid secretion was found among 3.2% of respondents. In nasal septum examination, septum deviation was found 6.5% to the right and 3.2% to the left. Conclusion: Most of the respondents showed normal resultKeywords: health survey, nose examinationAbstrak: Kesehatan pada manusia dapat dipengaruhi oleh lingkungan dan perilaku manusia. Hidung merupakan salah satu organ penting yang menjadi pelindung tubuh terhadap lingkungan yang tidak menguntungkan. Penelitian ini bertujuan untuk mengetahui gambaran kesehatan hidung pada masyarakat pesisir pantai Bahu. Desain yang digunakan ialah penelitian deskriptif survei dengan pendekatan potong lintang. Subjek penelitian ialah masyarakat pesisir pantai Bahu. Jumlah responden yang mengikuti penelitian ini 31 orang, terdiri dari 12 laki-laki dan 19 perempuan. Pada hasil pemeriksaan hidung didapatkan hasil normal pada 19 orang dan kelainan pada 12 orang. Pada pemeriksaan kavum nasal, kavum sempit ditemukan 3,2%. Pada pemeriksaan konka nasal, udim konka nasal 6,5%; udim dan pucat pada konka nasal 3,2%; udim, pucat, dan hipertrofi konka nasal kanan 3,2% dan konka nasal kiri 6,5%; udim, hiperemis, dan hipertrofi konka nasal 3,2%; hipertrofi konka nasal kanan 3,2% dan konka nasal kiri 6,5%; pucat dan hipertrofi konka nasal 3,2%. Pada pemeriksaan mukosa nasal, hiperemis mukosa 3,2%, dan livide mukosa 16,1%. Pada pemeriksaan sekret, serous dan mukoid 3,2%. Pada pemeriksaan septum nasal, deviasi septum ke kanan 6,5% dan ke kiri 3,2%. Simpulan: Sebagian besar responden penelitian ini memperlihatkan hasil normalKata kunci: survei kesehatan, pemeriksaan hidung